Development and validation of the analytical method by high performance liquid chromatography (HPLC) for Lamotrigine raw material - Guilherme Nobre Lima do Nascimento; Keyla Carla de Freitas Pereira; Hisao Nishijo; Tales Alexandre Aversi-Ferreira (Acta Scientiarum. Health Sciences, 2011)
Currently when all roads lead to the pursuit of total quality in production of drugs, it is essential to fully understand each phase of a production process. In this case, validation is the appropriate tool to ensure reliability of a production process involving new equipment and the analytical methodology, either in the pharmaceutical, food, computer, microelectronics area or any other area where the quality of the manufactured product is one of the main reasons for the existence of a given company. This study aimed to analyze the main aspects of the validation of analytical methods for Lamotrigine, new drug for bipolar disorder with wide use today. In conclusion, the proposed analytical method for determination of the lamotrigine content in raw materials is adequate, effective and capable of reproducing reliable results during analysis. This method is fast (running time of 10 minutes), selective, accurate, precise and robust for the determination of the drug, with no observed interfering substances in the optimum wavelength. It could be concluded that this may be a routine method for quality control laboratories to certify the quality of Lamotrigine.